Differences in the Management and Use of Health Services in Australia Using Publicly Available Data: Comparisons between New South Wales and Victoria - Jo M Martins; Godfrey Isouard (Asia Pacific Journal of Health Management)
Introduction: Differences in health service utilisation between States are noted in publicly reported data. The national averages for health service usage and health related actions in Australia may mask differences in the management and provision of health services among the states and territories. Although the utilisation of health services tends to rise with age, the extent of this and other factors has not been determined at the state level. This study will analyse these differences for the two largest states in Australia, New South Wales (NSW) and Victoria.